Implementation of social media marketing in the florist business - Wati, Pera; Zacky Aditiaga; Lingga Yuliana (Jurnal Ekonomi, 2024)
The purpose of this study is to examine how a florist uses social media for marketing purposes. Where this research identifies Kios Vana Florist as a case study. This study used descriptive qualitative method. The data collection method in this research uses interviews and documentation. Purposive sampling was used in the sampling technique where respondents worked at the Kios Vana Florist either as owners, marketers or content creators. The interview method includes methods used by someone for a specific purpose, trying to obtain information or opinions verbally directly from an informant. Documentation method is a data collection technique by collecting and analyzing documents, both written, image and electronic documents. The data analysis stages in this research include collecting data, transcribing data, identifying themes, analyzing themes, and presenting research results. The research results show that Kios Vana Florist has implemented social media marketing which can support its product marketing activities. The managerial implications in this research are that the Kios Vana Florist has not utilized Community Building optimally. This is very important because building a community can help social media marketers interact with their audience in a more personal and in-depth way.